2015
DOI: 10.1088/0954-3899/42/12/125005
|View full text |Cite
|
Sign up to set email alerts
|

${B}_{s,d}\;-\;{\bar{B}}_{s,d}$ mixings and ${B}_{s,d}\;\to \;{{\ell }}^{+}{{\ell }}^{-}$ decays within the Manohar-Wise model

Abstract: In this paper, we perform a complete one-loop computation of the short-distance Wilson data. We find that the Manohar-Wise model could explain the current data, especially when the couplings of the charged colour-octet scalars to quarks are complex, with the resulting χ 2 min being significantly smaller than that of the SM. Finally, we investigate correlations among the two isospin asymmetries ∆(K * γ) and ∆(ργ), as well as the averaged time-integrated branching ratios B(B s,d → µ + µ − ); some of them are fou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
92
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(97 citation statements)
references
References 125 publications
5
92
0
Order By: Relevance
“…Figures a and b show the morphology of erosion surfaces of 3YSZ and LMA‐3YSZ ceramics at 600°C. Many traces of plastic deformation in the erosion surface can be observed, and they can be explained by the fracture theory of elastoplastic indentation proposed by Evans . When the high‐speed corundum particles impact the ceramic materials at low temperatures, these particles may also cause some plastic scratches on the surface of targets to form the presented morphology.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figures a and b show the morphology of erosion surfaces of 3YSZ and LMA‐3YSZ ceramics at 600°C. Many traces of plastic deformation in the erosion surface can be observed, and they can be explained by the fracture theory of elastoplastic indentation proposed by Evans . When the high‐speed corundum particles impact the ceramic materials at low temperatures, these particles may also cause some plastic scratches on the surface of targets to form the presented morphology.…”
Section: Resultsmentioning
confidence: 99%
“…Many traces of plastic deformation in the erosion surface can be observed, and they can be explained by the fracture theory of elastoplastic indentation proposed by Evans. 26 When the high-speed corundum particles impact the www.ceramics.org/ACT Wear Resistance of LMA-3YSZ ceramic materials at low temperatures, these particles may also cause some plastic scratches on the surface of targets to form the presented morphology. The surfaces of 3YSZ and LMA-3YSZ ceramics may engender some plastic deformation areas underneath the abrasive particles when the particles impacted the surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…[52] On the other hand, it was reported that ecology factors could even change the photosynthesis pathway, and the photosynthesis of some plants can mutual transformation between C3 and C4 pathways. [51] [53] However, further study is still needed to clarify photosynthesis pathway of O. undulatifolius.…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, this free energy barrier must have both enthalpic and entropic origins, which are critically associated with the molecular structure and chain dynamics at microscopic length scales. But how exactly does a polymer chain with a 3D random coil conformation convert into predominately chain‐folded lamellar crystals? Likewise, people have also asked what would happen after the nucleation barrier is overcome? Whether the crystal could grow spontaneously and freely to a macroscopic scale size?…”
Section: Primary Nucleation and Crystal Growthmentioning
confidence: 99%